Determinan adopsi e-commerce dan dampaknya pada usaha mokro kecil dan menengah (UMKM) - Pangesti, Sinta Dwi; Adyaksana, Rahandhika Ivan (Journal of Business and Information Systems (e-ISSN: 2685-2543), 2021)
This study aims to determine the effect of organizational readiness, technological readiness and the external environment on e-commerce adoption and the effect of e-commerce adoption on the performance of MSMEs (Micro Small Medium Enterprises) in Sleman Regency. The sampling method used is purposive sampling. The data used in this study is primary data with data collection techniques using questionnaires. Hypothesis testing tool using SEM-PLS. Analysis of research data involving 150 in Sleman Regency. The results of hypothesis testing indicate a significant influence between organizational readiness on e-commerce adoption, technology readiness on e-commerce adoption, external environment on e-commerce adoption, and e-commerce adoption on MSMEs performance,